Popularization of IPM Practices for Management of Chickpea Pod Borer, through Frontline Demonstrations under Semi Arid Conditions - Khajuria, Shakti; Rai, A.K.; Kumar, Raj; Jadav, J.K.; Lata, Kanak (Indian Journal of Extension Education, 2016)
The present study was conducted to popularize the IPM practices for the management of chickpea pod borer through  frontline demonstrations in Panchmahals district of Central Gujarat. Constraints in chickpea production were identified  through participatory approach. Preferential ranking technique was utilized to identify the constraints faced by the  farmers in chickpea production. The results revealed that Helicoverpa armigera (Hubner) was the dominant chickpea  constraint ranked first followed by lack of knowledge about IPM (rank 2) and Agrotis ipsilon (rank 3). Fusarium wilt  (Fusarium oxysporum f sp ciceri) occupied the fourth rank. The extent of yield losses in chickpea were due to biotic  stresses, viz. H. armigera, Agrotis ipsilon, Fusarium wilt and stored grain insect pests was reported by the farmers. On the  basis of Rank Based Quotient (RBQ) and Value Based Index (VBI), it was found that H. armigera (VBI = 2303) is a major  threat to chickpea causing highest damage to the crop. Results indicate that IPM practices, application of bio-pesticides  i.e., HaNPVand neem oil revealed the best performance reduction in pod damage. The yield of chickpea in IPM practice  was 17.55 q/ha as compared to farmers practices (13.75 q/ha). The percentage increase in yield over farmer's practices  was computed to be 27.64. Results of study on economic analysis of the yield performance revealed that the IPM practices  recorded higher gross returns (` 43,875/ha) and net return (` 21,075/ha) with higher benefit cost ratio (1.92) as compared to  farmer's practices (1.62). Mean difference with respect to farmers' knowledge level after implementation of frontline  demonstrations increased to the tune of 33.13. The impact of frontline demonstrations was also analyzed which reflected  significant improvement in knowledge and satisfaction level on the part of farmers. Frontline demonstrations brings out  that the IPM practice is feasible and economically viable over farmers practice and is a better option to manage chickpea  pod borer using eco-friendly measures.
Keywords: Bio-pesticides; chickpea pod borer; IPM; Frontline Demonstration